Faktor-Faktor yang Berhubungan dengan Kejadian Diare pada Balita di Wilayah Kerja Puskesmas - Wakanno, Grace Jeny; Ivakdalam, Lydia Maria; Sahetapy, Joanna (MOLUCCAS HEALTH JOURNAL, 2023)
The prevention and transmission of diarrhea is still not fully realized by mothers, this causes many toddlers to experience diarrhea. The aim of this research is to determine the factors associated with the incidence of diarrhea in toddlers in the work area of the Pemaux Health Center. This type of research is quantitative using a cross sectional approach. The sampling technique used purposive sampling, the total population was 124 with a sample of 55 respondents who included the subject criteria. The results of research using the Chi-Square test showed that between maternal knowledge and the incidence of diarrhea in toddlers, the value was p=0.001 (p0.05), between economic income and the incidence of diarrhea in toddlers, the value was p=0.001(p0.05). , and between environmental sanitation and the incidence of diarrhea in toddlers, the value was p=0.000 (p0.05). So it can be concluded that the three variables above show that there is a significant relationship between maternal knowledge, economic income and environmental sanitation and the incidence of diarrhea in toddlers in the work area of the Supporting Health Center.Keywords: Diarrhea; Economy; Environment sanitation; Knowledge; Mother